Measurements of electron energy distribution in an argon positive column - Wong, C.S.; Chin, Oi Hoong; Eissa, M.A.; Gholap, A.V.; Mulyodrono, S.; Ong, C.X.; Sapru, S.; Saw, S.H.; Smith, A.J.; Sur'adi, -; Usada, W. (1986)
The argon positive column plasma of a cold cathode glow discharge is studied using a pulsed single Langmuir Probe technique. It is observed thatthe energy distribution of the electrons in the posotive column is non-maxwellian at a gas pressure of 0.5 mbar. An increase in the gas pressure seems to make the distribution more Maxwellian.